Calculation of the Damping Factors of the Flexible Pavement Structure Courses According to the In-place Testing Data. (2017) - Uglova, Evgeniya; Tiraturyan, Arem
Abstract: The paper demonstrates an approach to calculating damping factors of flexible pavement courses according to the operational in-place testing. The mechanical and mathematical simulation of the dynamic strain-stress condition of the multilayer semi-infinite space allows studying quantitative and qualitative relationship of wave field attenuation factors and mechanical parameters of pavement design courses. The paper presents the effect of the damping factors of pavement courses on the energy volume transferred to the pavement structure due to a standard vehicle passage.